2010
DOI: 10.1089/jwh.2010.1973
|View full text |Cite
|
Sign up to set email alerts
|

General Anxiety Disorder Symptoms, Tension Reduction, and Marijuana Use Among Young Adult Females

Abstract: Background: The current study tested the hypothesis that tension reduction expectancies mediate the relationship between anxiety symptoms and marijuana use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…Much of the research on negative affect associated with use has focused on anxiety, with evidence for the effect of anxiety on marijuana use being mediated by tension-reduction expectancies (de Dios et al, 2010) and coping motives for use (Johnson et al, 2009). EMA research with young, frequent marijuana users has suggested that the association between anxiety and subsequent marijuana use may be mediated by the effects of anxiety on craving (Buckner et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Much of the research on negative affect associated with use has focused on anxiety, with evidence for the effect of anxiety on marijuana use being mediated by tension-reduction expectancies (de Dios et al, 2010) and coping motives for use (Johnson et al, 2009). EMA research with young, frequent marijuana users has suggested that the association between anxiety and subsequent marijuana use may be mediated by the effects of anxiety on craving (Buckner et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…First, it is possible that we did not measure a covariate that explains this rapid increase in perceived norms over time. For example, researchers have suggested that youth may learn misperceived norms through viewing adolescent peers and young adults drinking on TV/movies, advertisements, and in pictures on social media websites such as Facebook (de Dios et al, 2010; Gordon et al, 2010; Perkins and Craig, 2003). We did control for age in our analyses, which by proxy may have been a factor related to increased media exposure (i.e., older youth may have more access to TV and social media).…”
Section: Discussionmentioning
confidence: 99%
“…Other work with both clinical and community samples of young adults has found that while social anxiety is positively associated with marijuana use and consequences, this relationship is stronger for those with negative expectancies (Buckner & Schmidt, 2008, 2009). Further research with young adult females has shown that tension reduction expectancies (i.e., marijuana makes me feel carefree and I do not care about my problems as much) mediated the association between anxiety and marijuana use (de Dios et al, 2010). Thus, studies that examine the association between mental health and marijuana use without considering expectancies may miss important qualifying information.…”
Section: Expectancy Theorymentioning
confidence: 99%